OCORRÊNCIA E USO DE RECURSOS ALIMENTARES POR PSITACÍDEOS NOS BIOMAS PANTANAL E CERRADO - Sabrina Cristiane Appel (2022)
Brazil is recognized worldwide as one of the richest countries in biodiversity. Among this richness are found more than 1,971 bird species, being considered the richest country of the world in parrot diversity, with a total of 87 species. Parrots constitute an emblematic group of species, as they can be used as a flag for the conservation of fauna and flora. Despite this, there is still a lack of scientific knowledge about several species of this family and regarding various aspects, such as the knowledge related to the use of food resources, as well as the adaptation of these birds to the urban environments. In this sense, this study aimed to investigate the occurrence and use of food resources by parrots from the Pantanal and Cerrado using online databases. Through bibliometric analysis, 19 species were verified for the Pantanal biome and 36 species of parrots for the Cerrado biome. For several species of parrots, especially the small ones, there is no information in the literature regarding the use of food resources. In general, it was observed that the species are dependent on native fruits from the Pantanal and Cerrado, even in urban areas. Therefore, the loss of natural habitats and the use of non-native species in afforestation can negatively impact the conservation of parrots.